Utilization of milk fatty acids by the suckling Iberian piglets. (5th May 2016) - Aguinaga, M. A.; Haro, A.; Lara, L.; Gómez-Carballar, F.; Nieto, R.; Aguilera, J. F.
Abstract : A total of 16 pure-bred Iberian (IB) sows, all of them suckling six piglets, were used, eight of them in each of the two consecutive trials (1 and 2). Daily milk yield and composition were determined weekly over a 34-day lactation period. Within each litter, one piglet at birth and four piglets on day 35 of life were slaughtered. Milk intake per piglet tended to be greater in trial 2 (832 v. 893 g/day; P =0.066), but piglets grew at 168±3.3 g/day, irrespective of the trial. In the IB sow milk, the linoleic (LA) : linolenic (LNA) acid ratio averaged 14.6 and 15.2 in trial 1 and trial 2, respectively. A fivefold increase in piglet body fat content was observed over lactation ( P <0.001). Most of this fat (81.4%) was present in the carcass. After 34 days of lactation, whole-body relative content of palmitic, palmitoleic, stearic and oleic acids were very close to those in the milk consumed, suggesting direct deposition. Daily deposition of LA derivatives and of LNA and its derivatives was found to be extremely low (<0.02 g, on average). Moreover, some of the arachidonic acid (ARA) in tissues of the IB piglet at birth disappeared throughout the lactating period. An overall fractional deposition for total fatty acids (FA) was 0.409. Fractional oxidation (disappearance) rates were 0.939 and 0.926 for n-6 and n-3 polyunsaturated FA. The overall rate of disappearance for the major non-essential FA (myristic, palmitic, palmitoleic, stearic and oleic acids), estimated as 1−the overall fractional deposition rate, was 0.546. It is concluded that the high degree of FA unsaturation, high oxidation rate of LA and LNA, and poor synthesis of ARA from LA and of docosahexaenoic acid from LNA found in the suckling piglet might increase the energy cost of whole-body fat accretion, a contributor to the observed low efficiency of use of milk energy for growth.